Mathematical Literacy of Junior High School Students in Solving Problems PISA in Minang Context - Fathur Rahmi; Iltavia Iltavia; Ramzil Huda Zarista (Universitas Muhammadiyah Mataram, 2022)
Often the use of repeated questions and answers is given by the teacher so that they cannot analyze students' mathematical literacy abilities. There needs to be a solution to the PISA problem so that student competencies can be seen clearly. The teacher should analyze this so that it does not happen continuously so that a way can be found to overcome it. The purpose of this study was to determine the mathematical literacy of junior high school students when working on PISA questions in the Minang context. This type of research is descriptive qualitative research. The results of the PISA test and interviews became the data in this study. To find out more detailed data, the authors took the research subjects based on the results of the PISA test later and categorized the subjects into the highest, medium and lowest. In this study, researchers used indicators of mathematical literacy level according to PISA. The results of this study indicate that in formulating the situation mathematically is 75%, reasoning 33.05% and solving problems 14.44%. That is, on average, students are only able to answer problems only up to level 2 PISA, that the ability to formulate situations mathematically.